Two new Augochlorine bees from Ecuador (Hymenoptera: Halictidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2007)
Two new species of augochlorine bees are described and figured from Ecuador. Caenaugochlora silvicola sp. n. is the first species of its genus with a relatively elongate malar space (although admittedly still shorter than true long-headed augochlorines) and can be readily distinguished from other Caenaugochlora by this trait as well as characters of coloration and integumental sculpturing. Caenaugochlora cuprina Moure & Hurd (= Augochlora cupriventris Friese), also from Ecuador, has proven to be a junior synonym of Megaloptilla callopis (Vachal) (syn. n.). Thus, C. silvicola sp. n. is the first true species of this genus formally documented from Ecuador. The secondspecies does not correspond to any known group of augochlorines and is placed in a new genus herein. Rhynchochlora chlerogopsis gen. et sp. n. is most similar to Chlerogas but differs in head, antennal, and mesoscutellar structure.
Keywords: čebele; Ekvador; entomologija; favna; nove vrste